PERLINDUNGAN HUKUM TERHADAP INVESTOR DALAM INVESTASI MELALUI REKSADANA SYARIAH DI IDONESIA - Arif Effendi (Institut Islam Mamba'ul 'Ulum Surakarta, 2020)
Arif Effendi, Legal Protection to Investors in Investment trough Sharia Reksadana (mutual funds) in Indonesia. This paper talk about legal protection to investors in Sharia Reksadana under sharia principles or Islamic law and Positive law in Indonesia. Reksadana is an instrument used to raise funds from the investor community to be reinvested in securities portfolio by the Investment Manager. Sharia Reksadana is a mutual fund that operates under the terms and principles of Islamic Sharia, either in the form of a contract between the owner of the property (sahib al-mal) and the Investment Manager as the representative of shahib al-mal, or between the Investment Manager as a representative of shahib al-mal with investment users. The operational mechanism in Sharia Reksadana between Investor and Investment Manager is done by wakala system. Meanwhile the operational mechanism between Investment Manager and Investment user (mudharib) is done by mudaraba system. Non-bank financial institutions such as Sharia Reksadana based on their operations using sharia principles. In that principle, prohibited all elements that are not in accordance with sharia. That are Riba (usury), Gharar (uncertainty), Maysir (gambling/speculation), etc. Wakala system, mudaraba system, and positive law agreement are needed to protect the investors. Profit sharing is the most appropriate system as a substitute for interest, to avoid riba (usuary). Sharia Reksadana is one of financial institutions that implements a system of profit sharing in the agreement in what we call mudaraba system. By implementing profit sharing sistem it is hoped to be free from riba (usury).